A Potential Role for Integrin-Linked Kinase in Colorectal Cancer Growth and Progression via Regulating Senescence and Immunity - Almasabi, Saleh; Ahmed, Afsar U.; Boyd, Richard; Williams, Bryan R. G. (Frontiers in Genetics, 2021)
Integrin-linked kinase (ILK) has been implicated as a molecular driver and mediator in both inflammation and tumorigenesis of the colon. ILK functions as an adaptor and mediator protein linking the extracellular matrix with downstream signaling pathways. ILK is broadly expressed in many human tissues and cells. It is also overexpressed in many cancers, including colorectal cancer (CRC). This has led to the hypothesis that targeting ILK therapeutically could have potential in CRC, as it regulates different cellular processes associated with CRC development and progression. A number of studies have indicated an ILK function in senescence, a cellular process that arrests the cell cycle while maintaining active metabolism and transcription. Senescent cells produce different secretions collectively known as the senescence-associated secretory phenotype (SASP). The SASP secretions influence infiltration of different immune cells, either positively for clearing senescent cells or negatively for promoting tumor growth, reflecting the dual role of senescence in cancer. However, a role for ILK in senescence and immunity in CRC remains to be determined. In this review, we discuss the impact of ILK on senescence and immunity, paying particular attention to the relevance of ILK in CRC. We also examine how activating Toll-like receptors (TLRs) and their agonists in CRC could trigger innate immune responses and subsequently prime adaptive cellular immunity against cancer, as a combination therapy with ILK inhibition.